TREATMENT OF OPEN PYOMETRA IN MINI POMMERANIAN DOG IN VETERINARY HOSPITAL HASANUDDIN UNIVERSITY - Waode Santa Monica; Eka Puteri Nurul Azizah Hidayat; Musdalifah; Rian Hari Suharto; Andi Tri Julyana Eka Astuty; Rifqatul Ummah; Kadek Dian Krisna Putrik; I Wayan Nico Fajar Gunawan (Buletin Veteriner Udayana, 2025)
Pyometra is a pathological condition in the female reproductive organs caused by a bacterial infection that leads to the accumulation of pus within the uterus. The aim of this article is to understand the diagnosis and management of pyometra in dogs. The diagnostic methods used include: anamnesis, physical examination, clinical examination, laboratory tests such as routine hematology and blood smear, as well as supporting examination through ultrasound. Examination Results:Anamnesis: A female Miniature Pomeranian dog, 8 years old, weighing 4.5 kg. The physical examination revealed lethargy, anorexia, and a reddish-brown vaginal discharge. Hematology results showed an increase in WBC, lymphocytes, monocytes, and granulocytes, while RBC, HGB, HCT, MCV, MCH, PCT, and PLT were decreased. Ultrasound findings: Enlarged uterus with a diameter of 5.7 cm due to the accumulation of fluid with hypoechoic-anechoic echogenicity (pus). The uterine wall was thickened with hyperechoic-hypoechoic echogenicity, leading to a diagnosis of open pyometra. Management involved an ovariohysterectomy procedure. During hospitalization, the following medications were administered: Azithromycin, Meloxicam, Furosemide, Sangobion, Mecobalamin, Curcuma Plus, Imboost, and Gold-G. A special diet of Royal Canin Recovery food was also provided. On the fifth day, the dog underwent reoperation due to wet surgical sutures and the accumulation of fluid in the abdominal area. After 10 days of treatment, the surgical site had dried, and the dog showed significant recovery, allowing it to be discharged for outpatient care.